Developing a Stabilizing Formulation of a Live Chimeric Dengue Virus Vaccine Dry Coated on a High-Density Microarray Patch - Jovin J. Y. Choo (MDPI AG, 2021)
Alternative delivery systems such as the high-density microarray patch (HD-MAP) are being widely explored due to the variety of benefits they offer over traditional vaccine delivery methods. As vaccines are dry coated onto the HD-MAP, there is a need to ensure the stability of the vaccine in a solid state upon dry down. Other challenges faced are the structural stability during storage as a dried vaccine and during reconstitution upon application into the skin. Using a novel live chimeric virus vaccine candidate, BinJ/DENV2-prME, we explored a panel of pharmaceutical excipients to mitigate vaccine loss during the drying and storage process. This screening identified human serum albumin (HSA) as the lead stabilizing excipient. When bDENV2-coated HD-MAPs were stored at 4 °C for a month, we found complete retention of vaccine potency as assessed by the generation of potent virus-neutralizing antibody responses in mice. We also demonstrated that HD-MAP wear time did not influence vaccine deposition into the skin or the corresponding immunological outcomes. The final candidate formulation with HSA maintained ~100% percentage recovery after 6 months of storage at 4 °C.